IMMUNOMODULATING EFFECTS OF ANTIBIOTICS IN CHICKENS - Jalaa A; Amaal F Jenan A; Hanadi M; Ali A.S.Al-Mayah; Deena H; Nagham Y. and Tamather A (Basrah Journal of Veterinary Research)
Evaluation of the effect of common antibiotics used in the farm production , on the immune system of chickens during the 21 days of life were investigated. A total of 60, one-dayold chicks were divided into Four equal groups and was raised for 30 days. Three groups were treated with Ampieillin, Enrofloxacin & Amoxyeillin respectively whereas the4"‘group was served as control. Antibiotic treatment was similar to regimen used in commercial chicken production. which included utilization of antibiotic at 1“ day of life and after vaccination. Body weight, bursa of fabrieius weight and bursa of fabrieius to body weight ratio were calculated in order to monitor the growth rate of bursa during the 2] days of life. All birds were vaccinated against ND at 7&2ldays of age. Blood samples were collected at l4&?.9 days of age. Blood total protein, albumin and globulin were determined. Antibiotic treatment often resulted in significant decrease (l’